2016
DOI: 10.1016/j.jtho.2016.08.134
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Cell Death Ligand 1 Expression in Resected Lung Adenocarcinomas: Association with Immune Microenvironment

Abstract: PD-L1 expression in resected lung adenocarcinomas is frequently observed in the presence of CTL/Th1 microenvironment, in particular in those with KRAS mutations or no common molecular alterations, suggesting that blockade of the PD-1/PD-L1 axis may be a promising treatment strategy to reinstitute active immune response for at least a subset of such patient populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 48 publications
9
61
0
1
Order By: Relevance
“…It is also noticeable that the extent of staining increases from those tumours that are lepidic‐predominant to those that are acinar/papillary‐predominant to those are solid/micropapillary‐predominant. This result is in agreement with other studies showing that solid components of ADCs have high PD‐L1 expression . Our data also correlate with several studies on the importance of a predominant pattern for prognostication in resected ADCs, and, should a grading system based on a predominant pattern and pleomorphic features be implemented, this might have predictive value in relation to the response to immunomodulatory therapy, in similar fashion to solid/micropapillary patterns having relevance in relation to the response to conventional chemotherapy in an adjuvant setting …”
Section: Discussionsupporting
confidence: 92%
“…It is also noticeable that the extent of staining increases from those tumours that are lepidic‐predominant to those that are acinar/papillary‐predominant to those are solid/micropapillary‐predominant. This result is in agreement with other studies showing that solid components of ADCs have high PD‐L1 expression . Our data also correlate with several studies on the importance of a predominant pattern for prognostication in resected ADCs, and, should a grading system based on a predominant pattern and pleomorphic features be implemented, this might have predictive value in relation to the response to immunomodulatory therapy, in similar fashion to solid/micropapillary patterns having relevance in relation to the response to conventional chemotherapy in an adjuvant setting …”
Section: Discussionsupporting
confidence: 92%
“…A fixed-effect model was employed due to no evident heterogeneity ( I 2 = 7%, P = 0.38), and the outcome revealed a significant correlation between PD-L1 expression and KRAS status (RR = 1.26; 95% CI, 1.06–1.50, P = 0.010, Figure 8A). Furthermore, the result mentioned above was obtained in the studies using PD-L1 McAbs (RR = 1.32; 95% CI, 1.06–1.65, P = 0.01, Figure 8B) [12, 13, 15, 16, 18]. However, subgroup analyses on the studies using PD-L1 PoAbs [14, 17, 21, 22] and on Chinese cohort studies [17, 18, 21, 22] displayed that no significant correlation between PD-L1 expression and KRAS status, (RR = 1.13; 95% CI, 0.87–1.48; P = 0.36, Figure 8C), (RR = 1.04; 95% CI, 0.74–1.47; P = 0.83, Figure 8D), respectively.…”
Section: Resultsmentioning
confidence: 69%
“…In lung adenocarcinoma, the presence of KRAS or the absence of targetable mutation are associated with PD-L1 expression, whereas EGFR or other common mutated adenocarcinoma rarely express PD-L1 [17]. A study in SC found that KRAS mutations are associated with PD-L1 expression, probably because these mutations are more likely to occur in smokers [3].…”
Section: Discussionmentioning
confidence: 99%